1996
DOI: 10.1063/1.116753
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of vertical cavity surface emitting laser by photoreflectance spectroscopy

Abstract: We report photomodulated reflectance results on vertical cavity surface emitting laser structures. Photoreflectance spectra have been recorded under normal incidence at different temperatures between 9 and 300 K. The structure used is a λ cavity grown in the AlGaAs-based system emitting at a wavelength near 800 nm. We show that photoreflectance is a unique noninvasive tool to measure accurately the quantum well transition and the cavity mode alignment: both features can be distinguished very well. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…In PR studies of full VCSEL structures, the excitonic signals are very strongly attenuated in the spectral region of the high reflectance stop band, unless they are in resonance with the cavity mode. 10,11 Therefore, one generally observes PR signals from only the cavity mode and the ground-state excitonic transition, but none from the higher-order transitions. An exception is the work of Moneger et al who detected higher-order QW transitions in an InGaAs/GaAs/AlGaAs VCSEL test structure, using contactless electroreflectance.…”
Section: Introductionmentioning
confidence: 98%
“…In PR studies of full VCSEL structures, the excitonic signals are very strongly attenuated in the spectral region of the high reflectance stop band, unless they are in resonance with the cavity mode. 10,11 Therefore, one generally observes PR signals from only the cavity mode and the ground-state excitonic transition, but none from the higher-order transitions. An exception is the work of Moneger et al who detected higher-order QW transitions in an InGaAs/GaAs/AlGaAs VCSEL test structure, using contactless electroreflectance.…”
Section: Introductionmentioning
confidence: 98%
“…So far, the mechanism giving rise to a cavity mode PR signal has been explained only qualitatively in terms of a laser induced modulation of the complex refractive index. 20,21 Here we present a detailed PR study of resonances between the cavity mode and QW excitons, particularly the ground-state exciton, in InGaAs/GaAs/AlAs VCSEL structures. We also focus on developing a model for the PR line shape of these signals.…”
Section: Introductionmentioning
confidence: 99%
“…11 Since real VCSEL's are generally designed to operate near room temperature, the cavity exciton resonance also occurs around 300 K. Unfortunately, previous reflectance studies on VCSEL's have shown that it is very difficult to observe clear excitonic signals in the complex R spectra near 300 K, even in the region of the flat high-reflectance stop band, [17][18][19][20][21] and there is only one report of Rabi splitting at ϳ300 K. 11 This can be overcome using modulation spectroscopy, in particular photomodulated reflectance ͑PR͒, where clear features related to both the cavity mode and QW transitions have been observed in VCSEL structures at room temperature. 20,21 However, to analyze such PR spectra fully, it is essential to be able to fit them with an appropriate line shape model, especially when several oscillatory features overlap, as is the case when the exciton and cavity modes are near to resonance. The theory of PR line shapes is well developed for excitonic transitions in bulk and heterostructure semiconductors ͑see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, photoreflectance ͑PR͒ yields, at room temperature, signals that make it possible to evaluate E QW , 4 -12 and in some cases E cav [5][6][7][8][9][10][11] as well as the built-in electric field in the i region from the Franz-Keldysh oscillations. 4 -9,12 Jaeger et al 13 have reported room temperature angle-dependent photocurrent spectroscopy that yields E QW and E cav .…”
mentioning
confidence: 99%